Design, Simulation and Construction of Field Effect Transistors - Vikraman, Dhanasekaran; Kim, Hyun-Seok (IntechOpen, 2018)
In recent years, research on microelectronics has been specifically focused on the proposition of efficient alternative methodologies and materials to fabricate feasible integrated circuits. This book provides a general background of thin film transistors and their simulations and constructions. The contents of the book are broadly classified into two topics: design and simulation of FETs and construction of FETs. All the authors anticipate that the provided chapters will act as a single source of reference for the design, simulation and construction of FETs. This edited book will help microelectronics researchers with their endeavors and would be a great addition to the realm of semiconductor physics.